Swallowing the sun: a novel - Puri, Lakshmi Murdeshwar; Author is an IFS (New Delhi Aleph Book, 2024)
Swallowing the Sun is an epic feat of remembering and storytelling. Through the eyes of its feisty young heroine, Malati, the novel recreates one of the most tumultuous periods in modern Indian history$1 (Bthe struggle for Independence. Malati$1 (Bs steeliness and fearlessness enable her to defy the constricting patriarchal traditions of her time and take on all those who try to cow her down. As a young girl, Malati fights and defeats the school bully of her village school in Maharashtra. From then onwards, backed by her progressive father, she and her sister Kamala push the boundaries constantly. After an eventful girlhood, the sisters become the first women in their family to go to college. They end up in Bombay, a hotbed of political ferment, where, even as she is whirled along by the irresistible current and excitement of the battle for Independence, she negotiates the small and big aspects of everyday life$1 (Blove, loss, failure, and compromise. Imaginative, compelling, and exquisitely told, Swallowing the Sun is one of the most memorable debut novels in recent years.s
Keywords: Fiction- English; Novel- English; IFS as an author